2021
DOI: 10.3390/microorganisms9040869
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Affects Expression of Circadian Clock Genes in Human Hepatoma Cells

Abstract: Recent research has indicated that dysbiosis of the gut microbiota can lead to an altered circadian clock of the mammalian host. Herein we developed an original system that allows real-time circadian studies of human HepG2 hepatoma cells co-cultured with bacteria. The HepG2 cells with stably integrated firefly luciferase reporter under the control of PERIOD2 promoter were co-cultured with E. coli strains isolated from human fecal samples from healthy individuals. The two E. coli strains differ in the phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
(42 reference statements)
0
9
0
1
Order By: Relevance
“…Circadian rhythms in pathogenic bacteria opens several research questions, including their involvement in host response and antibiotic resistance. Recently, Kovac et al showed that the genetic background of E. coli is important for the effect on mammalian circadian clock genes, indicating a possible future use of probiotic strains of E. coli to influence the host circadian clock [ 21 ]. Therefore, pathogenic bacteria could affect the circadian rhythm of the host immune system through their own rhythm.…”
Section: Resultsmentioning
confidence: 99%
“…Circadian rhythms in pathogenic bacteria opens several research questions, including their involvement in host response and antibiotic resistance. Recently, Kovac et al showed that the genetic background of E. coli is important for the effect on mammalian circadian clock genes, indicating a possible future use of probiotic strains of E. coli to influence the host circadian clock [ 21 ]. Therefore, pathogenic bacteria could affect the circadian rhythm of the host immune system through their own rhythm.…”
Section: Resultsmentioning
confidence: 99%
“…showed conflicting results. Analysis of log-ratios in the context of feature rankings and sample metadata was carried out using the Qurro tool [ 23 ]. Log-ratios of the selected taxonomic features associated with time across samples are provided on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic intervention is an innovative approach for the normalization of CRs. This has been evidenced by studies showing a positive restorative effect of probiotics and prebiotics on sleep quality [ 18 , 19 ] and circadian desynchrony [ 20 23 ]. Since GABA's central role for sleep has been well documented, its implication in this relationship cannot be completely dismissed.…”
Section: Introductionmentioning
confidence: 99%
“…Its effectiveness was explained by replacing toxic bacteria with normalized intestinal microflora. Escherichia coli based preparations were mainly used to treat and prevent intestinal dysbiosis [ 10 12 ]. Probiotic microorganisms must be able to multiply in the gastrointestinal tract actively.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment, virulent cultures of E. coli 15, S. Typhimurium 371, were used to infect experimental animals. The most important requirement for the manufacture and control of biological products is the production flow chart of the drug prepared from the E. coli 39-SN strain [ 9 – 12 ]. For the preparation of the E. coli strain 39-SN, the main digest of Hottinger was used, containing 10% of liver extract, 0.4% of peptone, then distilled water was added so that the content of amine nitrogen was at least 200–250 mg/% [ 13 – 16 ].…”
Section: Methodsmentioning
confidence: 99%